Pesantren Parenting as A Solution To Students' Moral Degradation (A Systematic Literature Review) - Wiyanto, Eko; Herpratiwi, Herpratiwi (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2024)
Education is actually not only a place for transferring knowledge, but also instilling positive personality values. So that education becomes a solution in answering the problem of moral degradation and various cases related to the morals of students. Pesantren (Islamic Boarding School) as the oldest educational institution in Indonesia has curriculum autonomy and the implementation of education is not only centered on knowledge, but also prioritizes the religious values and morals of students. This study aims to determine the effect of boarding schools as a solution to the problem of moral degradation. This study uses the Systematic Literature Review (SLR) method, with the research data in the form of 25 studies related to the role of Islamic boarding school parenting on the formation of morals for students. There are various methods of parenting applied by Islamic Boarding Schools, namely authoritarian parenting, democratic parenting, or a combination of both. The parenting provided starts from the transfer of knowledge, habituation of daily worship, personal advice, and the role of guardians as role models for students. The results of the analysis of the research data indicate that all studies are effective in shaping the positive character of students so that this parenting style can be a solution to the problem of students' moral degradation.